Coronary Artery Bypass Grafting: A Review of Short- and Long-Term Outcomes - Adeyemi, Adekemi; Berman, Lorin; Staroselsky, Mark; Cordero, Dessiree; Hai, Ofek; Makaryus, Amgad N.; Zeltser, Roman (International Journal of Angiology, 2025)
Coronary artery bypass grafting (CABG) remains a cornerstone in the management of complex coronary artery disease (CAD), offering significant improvements in both survival and quality of life. This review evaluates the short- and long-term outcomes associated with CABG. Despite its benefits, CABG carries perioperative complications, including atrial fibrillation, acute kidney injury, stroke, and surgical site infection. While early mortality rates, including in-hospital and 30-day outcomes, are comparable to those observed with percutaneous coronary intervention (PCI), long-term data often favor CABG in specific patient populations. Multiple studies have demonstrated superior long-term survival with CABG over PCI in patients with multivessel disease, left main CAD, and comorbid conditions such as diabetes mellitus. Perioperative morbidity and mortality are significantly influenced by patient-specific risk factors, such as advanced age, female sex, reduced ejection fraction, and elevated biomarkers (e.g., troponin, NT-proBNP, C-reactive protein). Since its introduction in the 1960s, CABG techniques have evolved with off-pump and minimally invasive approaches offering reduced hospital length of stay, shorter intensive care unit duration, and lower transfusion requirements, while maintaining comparable safety and efficacy to conventional on-pump surgery. In addition, graft selection is an important determinant of long-term success of CABG. In conclusion, CABG continues to be a highly effective revascularization strategy. Surgical technique, graft type, and careful patient selection remain essential to optimizing both perioperative safety and long-term outcome.
Keywords: coronary artery bypass grafting; coronary artery disease; surgical outcomes; perioperative complications; graft patency; long-term survival; postoperative mortality